Percutaneous coronary intervention for a healed erosion with excimer laser coronary angioplasty and drug-coated balloon angioplasty: a case report - Sekimoto, Teruo; Sato, Shunya; Mori, Hiroyoshi; Tanisawa, Hiroki; Tsujita, Hiroaki; Kondo, Seita; Suzuki, Hiroshi; Shinke, Toshiro (Frontiers in Cardiovascular Medicine, 2023)
Background: Healed plaque, characterized by distinct layers of organizing thrombus and collagen, is the hallmark of tissue self-repair. However, the efficacy of excimer laser coronary angioplasty (ELCA) followed by drug-coated balloon (DCB) angioplasty in patients with healed plaques is not fully understood. Case summary: A 42-year-old woman with a history of anxiety disorder was admitted to our institution with worsening chest pain and subsequently diagnosed with anterior non-ST-elevation myocardial infarction. Coronary angiography revealed severe stenosis in the proximal left anterior descending artery (LAD) despite Thrombolysis in Myocardial Infarction (TIMI) grade 3. Optical coherence tomography (OCT) showed healed plaques with partial macrophage accumulation and no fresh thrombus. Plaque disruption and thin-cap fibrous atheroma were not identified in the culprit lesions. Intravascular ultrasound (IVUS) confirmed high-intensity marginal irregular masses at the culprit site, suggesting that the thrombus was formed by plaque erosion rather than lipid plaque or necrotic tissue. With lesion modification using ELCA prior to DCB angioplasty, OCT examination of the LAD after ELCA showed a significant reduction in plaque burden and preserved lumen size. Post-percutaneous coronary intervention angiography revealed no stenosis with TIMI grade 3. A follow-up coronary computed tomography scan showed no angiographic restenosis, and the patient remained symptom-free. Conclusions: Here we describe a case in which OCT and IVUS evaluation suggested organizing thrombus due to erosion healing, and a favorable outcome was achieved with the combination of ELCA and DCB. The combination use of ELCA and DCB might be a potential strategy for acute coronary syndrome patients with organizing thrombus.